2012
DOI: 10.1007/s00210-011-0724-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dipyrone and thalidomide alone and in combination on STZ-induced diabetic neuropathic pain

Abstract: Diabetic neuropathy is recognized as one of the most common complications of chronic diabetes, but its pathophysiological mechanism is complex and yet to be completely explored. Monotherapy with conventional analgesics fails to provide adequate pain relief in peripheral diabetic neuropathy. There are a number of evidence suggesting that tumor necrosis factor (TNF-α) plays an important role in the pathogenesis of peripheral diabetic neuropathy. TNF-α up-regulation activates nuclear factor κB, which further up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 64 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…While previous studies have shown 18 that systemic administrations of thalidomide can strongly prevent the mechanical allodynia and thermal hyperalgesia in streptozotocin (STZ)-induced type 1 diabetic neuropathy (Chauhan et al, 2012;Huang et al, 2014;Taliyan and Sharma 2012), our study first demonstrated that supraspinal mechanisms of thalidomide play a critical role in modulations of type 2 diabetes induced neuropathic pain. Our results further suggested that TNFα and IL-1β mediated NFκB signaling in the RVM may contribute to the modulations of type 2 diabetes induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…While previous studies have shown 18 that systemic administrations of thalidomide can strongly prevent the mechanical allodynia and thermal hyperalgesia in streptozotocin (STZ)-induced type 1 diabetic neuropathy (Chauhan et al, 2012;Huang et al, 2014;Taliyan and Sharma 2012), our study first demonstrated that supraspinal mechanisms of thalidomide play a critical role in modulations of type 2 diabetes induced neuropathic pain. Our results further suggested that TNFα and IL-1β mediated NFκB signaling in the RVM may contribute to the modulations of type 2 diabetes induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, recent studies have shown that thalidomide can strongly prevent the mechanical allodynia and 5 thermal hyperalgesia in streptozotocin (STZ)-induced type 1 diabetic neuropathy (Chauhan et al, 2012;Huang et al, 2014;Taliyan and Sharma 2012). It has been reported that thalidomide can reduce the synthesis of TNFα and other pro-inflammatory cytokines including IL-1β (Sampaio et al, 1991;Singhal and Mehta 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, recent research has shown that thalidomide treatment can reduce thermal hyperalgesia and allodynia in an animal model of neuropathic pain (Cata, Weng, & Dougherty, ), and strongly attenuate the mechanical allodynia in an animal model of type 1 diabetic neuropathy (Chauhan, Taliyan, & Sharma, ; Huang et al, ; Taliyan & Sharma, ). These effects likely involve the RVM, since intra‐RVM thalidomide treatment was able to dose‐dependently decrease mechanical allodynia in diabetic rats (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It then returned to the market mainly as a treatment for myelodysplastic syndrome and multiple myeloma due to its anticachectic, antiemetic, mildly hypnotic, anxiolytic, antiinflammatory and antiangiogenic properties. Moreover, there are reports and studies of thalidomide for the treatment of inflammatory and nociceptive pains as an analgesic or analgesic adjuvant in clinic due to its immunomodulatory and anti-inflammatory properties (Asher and Furnish, 2013;Belda et al, 1966;Chauhan et al, 2012;Ching et al, 2003;Peuckmann et al, 2003;Ribeiro et al, 2000;Schwartzman et al, 2003). Thalidomide can selectively suppress the production of tumor necrosis factor α (TNF-α) (Andrade et al, 2012;Klausner et al, 1996;Marriott, 1997;McHugh and Rowland, 1997;Piura et al, 2013;Schmidt et al, 1996), which plays a pivotal role in the generation of pains.…”
Section: Introductionmentioning
confidence: 99%